Earliest evidence of nebular shock waves recorded in a calcium-aluminum-rich Inclusion. (1st September 2022) - Mane, Prajkta; Wallace, Shawn; Bose, Maitrayee; Wallace, Paul; Wadhwa, Meenakshi; Weber, Juliane; Zega, Thomas J.
Abstract: Calcium-aluminum-rich inclusions (CAIs) and chondrules are among the most predominant chondritic components contained within primitive meteorites. As CAIs are the first solids to form in the solar nebula, they contain a record of its earliest chemical and physical processes. Here we combine electron backscatter diffraction (EBSD) and 26 Al- 26 Mg chronology techniques to determine the crystallographic properties and ages of CAI components that provide temporal as well as spatial constraints on their origins and subsequent processing in the solar protoplanetary disk. We find evidence of shock deformation within a CAI, suggesting that it was deformed as a free-floating object soon after the CAI formation at the beginning of the Solar System. Our results suggest that even though CAIs and chondrules formed in distinct environments and on different timescales, they were likely affected by similar shock processes that operated over large temporal (0 to ∼4 Ma) and spatial (0.2 to at least 2 to 3 au) extents. Our results imply that nebular shock events were active on a wider scale in the solar protoplanetary disk than previously recognized.